Identifying the Solutions and Consequences of Preventing Students' Hate and Leaving of Sport - Sahar Pirjamadi; Reza Aminzadeh; Ahmad Mahmoudi; Zahra Hematyar (رشد و یادگیری حرکتی ورزشی, 2023)
Introduction: The present study was conducted with the purpose of identifying the solutions and consequences of preventing Students' Hate and Leaving of Sport.Methods: The purpose of the research was applied and the research method was qualitative. For this purpose, theoretical saturation was achieved with 21 experts in a purposeful judgment and using in-depth and semi-structured interviews. The data was collected using an exploratory approach through the identification process and its analysis using the qualitative software MaxQD. Also the retest reliability of the test was used.Results: In the current research, 104 indicators in the form of 14 concepts (use of knowledge and practice science, attention to personality-psychological characteristics, development of public sports, elimination of inappropriate habits in sports environments, advertising and promotion, economic, facilitating access, role of government and officials, Increasing participation, increasing awareness, improving the physical-psychological condition of society, changing beliefs, professional development, educational development) were identified.Conclusion: The current research emphasizes on the factors of motivational strategies, culture building, structural strategies, acculturation of sports in the society, increase of public health and development of sports infrastructures in preventing students from hating and practicing sports. In this context, paying attention to factors such as the construction and location of sports facilities in the school environment, increasing the hours of physical education in schools, preparation of sports programs on radio and television, holding morning sport programs, invite famous sport figures and offer discounts to teenagers in order to prevent students from hating and leaving of sport it is suggested.